2013
DOI: 10.31729/jnma.2440
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi- Fujimoto Disease of Mesenteric Lymph Nodes Mimicking Acute Appendicitis

Abstract: Kikuchi-Fujimoto disease, or histiocytic necrotising lymphadenopathy of unknown aetiology, is a rare, benign and self-limiting cause of lymphadenopathy often involving the cervical nodes, and rarely presenting with mesenteric lymphadenopathy. We present a 26-year-old Caucasian male, who presented with right iliac fossa pain and low grade pyrexia, mimicking acute appendicitis. He underwent a laparatomy and an extended right hemi-colectomy for a caecal mass. Histology of the specimen showed lymph nodes with exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…If there was no manifestation of an acute abdominal pain, the affected lymph node might not be excised through surgery in time, and the diagnosis process of KFD might be more tortuous. Three KFD cases involving mesenteric lymph nodes and causing acute-appendicitis-like symptoms were reported, and the patients were adults who underwent appendectomy with excision of an enlarged mesenteric lymph node and were diagnosed as KFD based on histopathological findings (16)(17)(18). The pathological features showed lymph node has architecture with partial follicular hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…If there was no manifestation of an acute abdominal pain, the affected lymph node might not be excised through surgery in time, and the diagnosis process of KFD might be more tortuous. Three KFD cases involving mesenteric lymph nodes and causing acute-appendicitis-like symptoms were reported, and the patients were adults who underwent appendectomy with excision of an enlarged mesenteric lymph node and were diagnosed as KFD based on histopathological findings (16)(17)(18). The pathological features showed lymph node has architecture with partial follicular hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Extracervical disease especially with bilateral cervical adenopathy and leukopenia in a review of 60 patients (mean age of 21years) with confirmed KFD manifested with abdominal in 52%, pelvic in 47%, inguinal in 41%, and axillary lymph nodes in 30% of patients, respectively[ 78 ]. Mediastinum lymphadenopathy can occur more often while the involvement of mesenteric lymphadenitis is rare and often mimic appendicitis[ 79 - 82 ]. However, nodal enlargement may be minimal or remain limited to mediastinal or retroperitoneal nodes only[ 83 , 84 ].…”
Section: Clinical Featuresmentioning
confidence: 99%